Skilled players cooperate less in multi-player games - Chesney, T.; Chuah, S.; Hoffmann, R.; Hui, Wendy; Larner, J. (Intellect Ltd, 2014)
A naturalistic public good experiment is used to examine whether better players cooperate more or less than others. ‘Better’ is measured by subjects’ accuracy in a team-based shooting game, and cooperation is measured by introducing a public good decision into the game. A data set of 92 subjects was created and results show that better players cooperate significantly less than others. Economic theory is used to explain the result.